2010
DOI: 10.1097/aud.0b013e3181b7190c
|View full text |Cite
|
Sign up to set email alerts
|

Information From the Voice Fundamental Frequency (F0) Region Accounts for the Majority of the Benefit When Acoustic Stimulation Is Added to Electric Stimulation

Abstract: Objectives The aim of this study was to determine the minimum amount of low-frequency acoustic information that is required to achieve speech perception benefit in listeners with a cochlear implant in one ear and low-frequency hearing in the other ear. Design The recognition of monosyllabic words in quiet and sentences in noise was evaluated in three listening conditions: electric stimulation alone, acoustic stimulation alone, and combined electric and acoustic stimulation. The acoustic stimuli presented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
208
8
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(234 citation statements)
references
References 35 publications
16
208
8
2
Order By: Relevance
“…The top performer, CI-2, had a number of advantages, including professional knowledge of hearing and assistive technologies as well as residual low-frequency hearing (at 250 and 500 Hz) in his unimplanted ear, which was selectively amplified. Zhang, Dorman, and Spahr (2010) have documented the contribution of low-frequency acoustic hearing to the recognition of monosyllabic words.…”
Section: Open-set Word Recognitionmentioning
confidence: 99%
“…The top performer, CI-2, had a number of advantages, including professional knowledge of hearing and assistive technologies as well as residual low-frequency hearing (at 250 and 500 Hz) in his unimplanted ear, which was selectively amplified. Zhang, Dorman, and Spahr (2010) have documented the contribution of low-frequency acoustic hearing to the recognition of monosyllabic words.…”
Section: Open-set Word Recognitionmentioning
confidence: 99%
“…Referred to variably as electric-acoustic stimulation (EAS) or bimodal hearing, this configuration involves the use of residual low-frequency acoustic hearing in the ear either ipsilateral or contralateral to the CI (Gifford et al, 2010). The improvements to intelligibility in noise with this strategy are well-documented (e.g., von Ilberg et al, 1999;Gantz and Turner, 2004;Gantz et al, 2005;Kong et al, 2005;Gifford et al, 2007;Dorman et al, 2008;Brown and Bacon, 2009a;Zhang et al, 2010). Dorman et al (2008) reported that, in a babble background at a S/N of þ5 dB, CI users' sentence recognition improved by an average of 22 percentage points with the addition of contralateral acoustic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…and (b) Do low-frequency information and high-frequency information play different roles for CI and bimodal listeners in terms of bandwidth extension to improve their perception of telephone speech? It should be noted that a few other studies assessed the effect of limiting the information accessible to bimodal users by either low passing the acoustic stimuli (Zhang et al, 2010b), or high passing the electric stimuli and low passing the acoustic stimuli (Zhang, Dorman, & Spahr, 2010a). They showed that the F0 was the beneficial cue for the bimodal benefits in speech recognition in noise by electroacoustic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (see, e.g., Dorman, Gifford, Spahr, & McKarns, 2008;Gantz, Turner, & Gfeller, 2006;Hu & Loizou, 2010;Kiefer et al, 2005;Kong, Stickney, & Zeng, 2005;Turner, Gantz, Vidal, Behrens, & Henry, 2004;von Ilberg et al, 1999) have documented the improved speech intelligibility, especially in noise, when low-frequency acoustic sound is added to the electrical information presented by the CI. These benefits were at least partly attributed to a better representation of F0 cues from the lowfrequency acoustic energy (see, e.g., Chang, Bai, & Zeng, 2006;Hu, 2010;Qin & Oxenham, 2006;Zhang, Dorman, & Spahr, 2010b). The presence of variation in the F0 has been shown to be a useful cue for bimodal listeners for identifying word boundaries, thereby facilitating lexical segmentation (Spitzer, Liss, Spahr, Dorman, & Lansford, 2009).…”
mentioning
confidence: 99%